THE EFFECT OF SELF-ACUPRESSURE ON REDUCING BLOOD PRESSURE, HEADACHE AND SLEEP QUALITY DISORDERS IN HYPERTENSIVE PATIENTS - Sri Mumpuni Yuniarsih; Nunung Hasanah; Rahajeng Win Martani; Umum Afifah (International Journal of Islamic and Complementary Medicine, 2024)
Hypertension is still a major health problem in Indonesia. Various efforts to overcome the problem of hypertension have been made, both pharmacological and non-pharmacological treatments. A therapy based on the patient's habits or culture will certainly be easier to implement and obey by. Therefore, this study aims to analyze the effect of self-acupressure on blood pressure, headache, and sleep quality of hypertensive patients. The research method used is a quasi-experiment, single-group pre-post-test design. The sample in this study were hypertensive patients who fit the inclusion and exclusion criteria at Wonokerto Health Centre, Pekalongan Regency. The data analysis used was univariate and bivariate analysis. Bivariate analysis used paired group t-test technique. The results showed that there was an effect of self-acupressure in reducing systolic blood pressure (p-value: 0.004), headache pain scale (p-value: 0.001), and decreased sleep quality disorder score (p value: 0.000). Massaging at acupressure points has the effect of improving blood flow, stimulating endorphin hormones and providing a relaxing effect so that it can reduce blood pressure, headache pain scale and sleep quality disturbance scores. Recommendations for future research are to add a control group and/or compare it with other independent complementary therapy techniques.